Desenvolvimento e validação de questionário específico para a avaliação da qualidade de vida em pacientes com fibrilação atrial - Braganca, Erika Olivier Vilela [UNIFESP] (2009)
O autor só colocou Abstract -Background: Atrial fibrillation (AF) is the most common sustained arrhythmia in clinical practice, and has major impact on health-relatedquality of life, thus, there is a need for a specific instrument to assess AF symptoms and quality of life. Methods: We developed and validated a specific questionnaire for quality of life inAF patients (QLAF) based on clinicalmanifestations (palpitation,breathlessness, dizziness and chest pain), and the usual treatments (medication, cardioversion and ablation). For validation, the new questionnaire was compared with the generic SF-36 questionnaire. Reproducibility was tested using 40 questionnaires administered by two different observers at distinct times and places. Responsiveness was evaluated based on variation of the QLAF score over time. Results: There were a total of 462 questionnaires (231 SF-36 and 231 QLAF) administered at baseline, 3, 6, 9 and 12 months. Construct validity was demonstrated by the negative correlation between QLAF and SF-36 scores that was observed over the follow-up period. Analysis of internal consistency for reproducibility showed excellent Cronbach's alpha coefficients (inter- and intraobserver coefficients of 0.98 and 0.96, respectively). QLAF was responsive as indicated by significant differences in mean domain scores from the beginning to the end of follow-up. It took much less time to administer the QLAF than the SF-36 (3:08±0:33 min vs. 9:25±1:14 min, pb0.001). Conclusion: The QLAF questionnaire is easy to understand and can be administered rapidly in the outpatient setting. Furthermore, the QLAF score is valid and reproducible and responsive to a change in clinical status..